Analisis Pola Penggunaan Remitan Migrasi Internasional Secara Produktif dan Konsumtif di Kabupaten Malang - Mustapita, Arini Fitria; Rizal, Mohammad (Universitas Islam Malang, 2017)
International Migration can positively impact the formation of remittances. Remittance is one of the tools in the economic improvement of migrant families. Remittances are not only money or goods, but also ideas. Based on the priority of its use, there are several patterns of use of remittance that is productive pattern oriented to activities that can form the accumulation of assets in the future and will have an impact at the macro level on development in the area of origin and consumption patterns are more oriented to the short term that will provide micro impact. The purpose of this study is to see the characteristics of migrants that affect the level of delivery remittance and see usage patterns of remittances in District Bantur Malang. The analytical tool used in this study is the percentage of analysis and the results showed the level of remittance delivery is influenced by several characteristics of migrants, such as type of work, length of working and the destination country. The characteristics that can affect the level of the International Migration salary that can also affect the rate of delivery of remittances. Based on the priority of use, patterns of use of remittances consumptive in District Bantur Malang include expenses of daily necessities, purchase electronic goods, home renovation and pay the debt, and the usage patterns of productive in District Bantur Malang include investment in childrens education, the purchase of land (farm / Land), purchase of livestock and venture capital investment.